The Biography and Creative Work of Amy Tan - Matyokubova Shukurjon Farhodovna (Genius Journals, 2022)
The Chinese American literature originated in the 1850’s when the first Chinese immigrants reached America and wanted to share their experience with other people. The early Chinese works depict American history from a point of view of immigrants to the United States, using their Chinese background for comparison with the American reality.
Keywords: Odd jobs; novels; awards and books